2014
DOI: 10.1111/jocn.12605
|View full text |Cite
|
Sign up to set email alerts
|

Australian practice nursing: collaboration in context

Abstract: Collaborative interprofessional care in Australian general practice must occur if increased demands for care are to be met. It is timely to consider how government policy, financial regulations and the organisation of Australian general practice can better support and enhance a collaborative contribution to care by practice nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…While many of the interventions were supported by research funding, their sustainability is dependent on funding models to remunerate general practices for nurse time (Halcomb, Furler, et al., ; Zwar et al., ). The move in Australia away from item based funding to block funding is a step toward creating a model that allows primary care nurses to provide the type of nursing services that are required in primary care (Merrick et al., ). A similar system operates in the UK and New Zealand where a government funded fee for service model supports the primary care nurse's role (Hoare, Mills, & Francis, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of the interventions were supported by research funding, their sustainability is dependent on funding models to remunerate general practices for nurse time (Halcomb, Furler, et al., ; Zwar et al., ). The move in Australia away from item based funding to block funding is a step toward creating a model that allows primary care nurses to provide the type of nursing services that are required in primary care (Merrick et al., ). A similar system operates in the UK and New Zealand where a government funded fee for service model supports the primary care nurse's role (Hoare, Mills, & Francis, ).…”
Section: Discussionmentioning
confidence: 99%
“…This evolutionary path has seen marked changes in defining primary care nurses from primarily a receptionist or assistant (Condon, Willis, & Litt, 2000) to a key health professional in the primary care team (Australian College of Nursing 2015). Despite this professional growth, the full potential and contribution of primary care nurses remain underdeveloped (Halcomb, Salamonson, Davidson, Kaur, & Young, 2014;McInnes, Peters, Bonney, & Halcomb, 2015;Merrick, Fry, & Duffield, 2014).…”
mentioning
confidence: 99%
“…). While GPN T2DM consultation is recognised as enhancing the patient experience of care, Merrick's () exploration of GPN collaboration in the context of patients with chronic disease found that due to the increased demands for chronic care, new ways of working need to be fostered to better support teamwork and enhance the GPN collaborative contribution to optimal patient health outcomes (Merrick et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 study in the Netherlands employing quality assessment of practice nurses' communication about type 2 diabetes, using a similar consultation approach to this study, found gaps in selfmanagement support and suggested that nurses would benefit from care delivery using standardised models of behavioural change counselling to enhance patient outcomes (Mulder et al 2015). While GPN T2DM consultation is recognised as enhancing the patient experience of care, Merrick's (2014) exploration of GPN collaboration in the context of patients with chronic disease found that due to the increased demands for chronic care, new ways of working need to be fostered to better support teamwork and enhance the GPN collaborative contribution to optimal patient health outcomes (Merrick et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As a result twenty-five semi-structured questions were developed to explore and explain decisionmaking processes, experience of support from supervisors and colleagues, and perceptions of role structure within the organisation (Merrick, Fry, & Duffield, 2014). The results of both studies were integrated utilising a pragmatic approach to inquiry to develop a nested understanding of causal mechanisms.…”
Section: Methodsmentioning
confidence: 99%